Free trade and commercial opening in the pacific alliance and economic impact: Period 1970 - 2015 - Ríos Zuta, Hoover (2019)
Objective: Put into perspective free trade and its impact on trade liberalization with the Pacific Alliance bloc. A balance has been made of the main aspects related to the international trade of this block during the last 45 years which marked a new stage of commercial relevance for the economic development of these countries; and from Latin America. Method: The type of research used was of an experimental type, with a transactional or cross-sectional design. Regarding its quantitative dimension, this work seeks to find solutions throughout its execution process.